Implementation of internal laboratory quality control procedures for the monitoring of ELISA performance at a regional veterinary laboratory. - Blacksell, S; Cameron, A; Chamnanpood, C; Chamnanpood, P; Tatong, D; Monpolsiri, M; Westbury, H (1996)
Quality control (QC) procedures for antigen detection enzyme-linked immunosorbent assays (ELISAs) for hog cholera (HC) virus, foot and mouth disease (FMD) virus, and an antibody detection ELISA for FMD virus were established at a regional veterinary laboratory in northern Thailand. A recently developed computer software package, QCEL, was used to facilitate management and analysis of QC data. The program was used to assess test performance by producing Shewhart-CUSUM control charts which monitored control data for unacceptable fluctuations or trends. QCEL-generated control charts and analyses are presented and discussed. The use of a simple integrated computerised system for storage and analysis of QC control data provided the laboratory with the opportunity to achieve increased confidence in the results of tests performed.